Vital media : making, design, and expression for humans and other materials - Nitsche, Michael (The MIT Press, 2022)
A proposal for a new media design to balance the contributions of humans and materials in the world they share. How can media design support a balance between our needs for self-expression and the material needs of the world we are part of? What criteria define a sustainable media ecology? In Vital Media, Michael Nitsche argues that the current human-centric view is not sustainable and that media are best viewed as dynamic networks where cognitive and noncognitive participants co-create. What we need, according to Nitsche, is a media design that balances the needs of all partners involved: vital media. Tracing this ideal through two domains of expression and making, performance and craft, Nitsche calls on us to embrace material coexistence and to design for self-expression as well as material evolution. We must recognize that the living body and its dependencies on the world around it are at the heart of what media are about. Vital media exist to not only help individuals fulfill their potential through expression but to also realize the agencies of materials in the equally active surrounding world. Throughout the book, Nitsche interweaves theory with close readings of actual artifacts that encompass predigital, nondigital, and hybrid examples. Nitsche's approach counters the current tendency to pit the virtual media world against the reality in which we live.